Keunggulan Bersaing Usaha Mikro Hasil Olahan Belimbing Usaha Dagang Cemara Sari Berbasis Inovasi Produk di Kota Blitar - Arianto, Novia Wahyu Arianto; Wahyudi, Edy Wahyudi; Iswono, Sugeng (e-Sospol)
AbstractThis research was conducted to find out and describe the Competitive Advantages in Small Firms Assorted Starfruits Product of Cemara Sari Trading Business Based on Product Innovation At Blitar City This research was carried out on UD Cemara Sari who innovate with processed star fruit-based product innovation. This research used a qualitative approach to research methodology, and use methods of snowball method in determining the informant. Informants in this study were three people associated with the competitive advantage and innovation-based products. The analysis of the data used is a domain analysis and taxonomy. The results showed indications that competitive strategy of Porter can be done on a micro scale, efforts in this research is the UD Cemara Sari. This can be evidenced by the results of the research done that companies were able to adapt the concept of competitive advantage strategy, focus, low cost and differentiation. The company also has done an innovation based on modulation products, innovation based on size, innovation based on packaging, innovation based on design, innovation based on development of complementary material, and innovation based on reduction costumer efforts. These innovations are based on intuition and impulse from the business owner to be able to create new products as a competitive company value. By innovating their products, firm can increase its advantages and became a leader in the environmental industry of assorted starfruit product at Blitar.